France before 1789 : the unraveling of an absolutist regime - Elster, Jon, 1940- (Princeton University Press, 2020)
"France before 1789 presents the main features of the prodigiously complex social system of the ancien regime which proceeded the French Revolution. In doing so Jon Elster goes beyond formal institutions to show how they worked in practice. He draws on a host of examples and contemporary texts to illuminate the perverse and sometimes pathological effects of this system and seeks to provide a detailed analysis of the political institutions that undergirded it. Whereas Tocqueville, in his famous analysis of the ancient regime, wanted to understand the old regime as a prelude to revolution, Elster views it as a prelude to constitution-making prompted by and intended to resolve these perversities. He views these as overlapping, yet important enough to render distinct. In addition to defending a particular set of substantive propositions about the conditions which led to the Constituent Assembly, Elster argues for a specific methodological approach to history, which emphasizes supplementing the historian's craft with approaches from the social sciences. Ultimately, he does not claim to answer the historians' questions better than they do. But he does aspire to ask and sometimes answer questions that historians have not formulated in order to better understand one of the most significant examples of collective decision-making history offers us"-- Provided by publisher.
Keywords: Social groups -- France -- History -- 18th century.; Social psychology -- France -- History -- 18th century.; Political psychology -- France -- History -- 18th century.; France -- Social conditions -- 18th century.; France -- Politics and government -- 18th century.; Psychologie sociale -- France -- Histoire -- 18e siècle.; Psychologie politique -- France -- Histoire -- 18e siècle.; France -- Conditions sociales -- 18e siècle.; France -- Politique et gouvernement -- 18e siècle.; PHILOSOPHY / Political; Political psychology; Politics and government; Social conditions; Social groups; Social psychology; France; 1700-1799; American Revolution.; Charles Tilly.; Democracy in America.; European history.; French Revolutionary Wars.; French history.; Georges Lefebvre.; Jon Elster.; Jonathan Israel.; Napoleon.; Napoleonic France.; Napoleonic era.; Philip Hoffman.; R. R. Palmer.; The Age of the Democratic Revolution.; The Old Regime and the Revolution.; constitutionalism.; history of France.; psychology of emotion.; revolutionary history.; social science.; sociology of collective action.; History